2023
DOI: 10.1128/spectrum.04625-22
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acyl Coenzyme A Synthetase Fat1p Regulates Vacuolar Structure and Stationary-Phase Lipophagy in Saccharomyces cerevisiae

Abstract: The ability to sense environmental changes and adjust the levels of cellular metabolism is critical for cell viability. Autophagy is a recycling process that makes the most of already-existing energy resources, and the vacuole/lysosome is the ultimate autophagic processing site in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Vacuole fusion and lipophagy do not rely on the same molecular machinery [ 2 , 11 , 38 , 39 ]. Still, both processes are related via lipid transport activities, as for example Fat1, a fatty acyl coenzyme A synthetase and fatty acid transporter, was recently shown to regulate vacuole fusion and morphology but also lipophagy in stationary phase [ 40 ]. When assessing the relationship between droplet uptake and vacuole morphology, we found that fluorescence of the droplet marker BODIPY493/503 is inside and outside of the vacuole for both, fully and partially fused vacuoles ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vacuole fusion and lipophagy do not rely on the same molecular machinery [ 2 , 11 , 38 , 39 ]. Still, both processes are related via lipid transport activities, as for example Fat1, a fatty acyl coenzyme A synthetase and fatty acid transporter, was recently shown to regulate vacuole fusion and morphology but also lipophagy in stationary phase [ 40 ]. When assessing the relationship between droplet uptake and vacuole morphology, we found that fluorescence of the droplet marker BODIPY493/503 is inside and outside of the vacuole for both, fully and partially fused vacuoles ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from Ncr1 and Npc2, there are other proteins which are essential for both, vacuole fusion and morphology as well as turnover of LDs during stationary phase: Fat1 is well known to mediate import of fatty acids into yeast cells but it also locates to LDs and has recently been described to regulate vacuole fusion and morphology during starvation [ 40 , 97 ]. Since Fat1 also possesses very-long-chain acylation activity, it was suggested to control vacuole morphology, fusion and lipophagy by regulating the fatty acyl chain composition of phospholipids in the vacuole membrane [ 40 , 97 ]. Recent analysis of the lipid composition of vacuoles isolated from log- and stationary-phase grown yeast indeed found an increase in saturated phospholipid species during starvation [ 71 ].…”
Section: Discussionmentioning
confidence: 99%